Strategy for Developing MSMEs to Support the Halal Tourism Sector in Banda Aceh City - Jalilah Jalilah; Isnaliana Isnaliana; Inayatillah Djakfar; Dara Amanatillah (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in supporting regional economic development, including in the advancement of halal tourism in Aceh. Banda Aceh, as the center of economic and religious tourism activities, holds great potential to become a model of a halal tourism city based on Islamic values. However, this potential has not been fully optimized due to various challenges in strengthening the capacity and halal certification of MSME actors. This study aims to analyze the development strategies of MSMEs in supporting the halal tourism sector in Banda Aceh City. The research employs a qualitative approach with descriptive analysis methods. Data were collected through interviews with several relevant parties, including MSME actors in Banda Aceh and Aceh Besar, the Aceh Office of Cooperatives and MSMEs, the LPPOM-MPU Aceh, and the Aceh Department of Culture and Tourism. Secondary data were obtained through library research from various literature sources, media, and academic journals. The results indicate that strengthening the halal tourism sector largely depends on the active role of MSMEs in providing high-quality halal products. The strategies that need to be implemented include enhancing halal literacy and education, accelerating the halal certification process, establishing institutional synergy, expanding market access and product digitalization, and facilitating access to Sharia-based financing. The implementation of these strategies is expected to position Banda Aceh as a leading halal tourism destination while strengthening the community's economy based on Islamic principles.